1993
DOI: 10.1073/pnas.90.21.10250
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between NMR transverse relaxation, trabecular bone architecture, and strength.

Abstract: Structure, biomechanical competence, and incremental NMR line broadening (R') of water in the intertrabecular spaces of cancellous bone were examined on 22 cylindrical specimens from the lumbar vertebral bodies of 16 human subjects 24-86 years old (mean, 60 years old). A strong association (r = 0.91; P < 0.0001) was found between Young's modulus of elasticity and R' for a wide range of values corresponding to cancellous bone of very different morphologic composition. NMR line broadening is caused by the inhomo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
100
1

Year Published

1999
1999
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 137 publications
(105 citation statements)
references
References 18 publications
4
100
1
Order By: Relevance
“…Surfaces were modeled with triangular elements of constant magnetic surface charge density, which allows the induced field to be computed from eqn (5). The data indicated the width of the induced field distributions to be narrowest for the polarizing field applied parallel to the preferred orientation of the trabeculae, confirming previous experimental findings (40). Figure 2 shows a histogram of the induced magnetic field, derived from 3D MR images of bovine tibia with the magnetic field oriented along each of three orthogonal directions.…”
Section: Nature Of the Susceptibility-induced Fieldsupporting
confidence: 76%
See 2 more Smart Citations
“…Surfaces were modeled with triangular elements of constant magnetic surface charge density, which allows the induced field to be computed from eqn (5). The data indicated the width of the induced field distributions to be narrowest for the polarizing field applied parallel to the preferred orientation of the trabeculae, confirming previous experimental findings (40). Figure 2 shows a histogram of the induced magnetic field, derived from 3D MR images of bovine tibia with the magnetic field oriented along each of three orthogonal directions.…”
Section: Nature Of the Susceptibility-induced Fieldsupporting
confidence: 76%
“…The relationship between the locally induced fields and architecture (density and orientation of the trabeculae), begs the question whether R Ã 2 or R 0 2 can serve as a surrogate for the bone's mechanical competence. Several studies have investigated this aspect by comparing the elastic modulus or ultimate strength measured by mechanical testing, with R 0 2 or R Ã 2 (40,47,48). As pointed out previously, the TB structure is highly anisotropic and, as expressed by eqn (6), R 0 2 has a strong angular dependence.…”
Section: Nature Of the Susceptibility-induced Fieldmentioning
confidence: 99%
See 1 more Smart Citation
“…While both NMR and magnetic resonance imaging (MRI) have been used to characterize bone in a number of studies [40,45,[48][49][50][51][52][53][54][55][56], the present work is the first to quantify water distribution in bone for two age groups. A previous study had actually characterized water distribution in dentin samples from a 20 year, 35 year, and 50 year old donor [50].…”
Section: Discussionmentioning
confidence: 99%
“…However, it is well known that BMD is not the sole determinant of bone strength and that architecture plays a significant role in conferring strength to the trabecular network (6)(7)(8). Unlike bone mineral densitometry, which affords a measure of global or regional bone density, we and others have shown that magnetic resonance microimaging ( -MRI) can quantify trabecular bone microarchitecture in vitro in specimens and biopsies (9)(10)(11)(12)(13) and in vivo in laboratory animals and humans (14)(15)(16). Whereas microcomputed tomography ( -CT) can generate high-resolution images of trabecular bone architecture (17), magnetic resonance (MR) is unique in that it is also able to provide detailed information on structure and function of soft tissues and bone marrow, which are also affected by steroid treatment.…”
mentioning
confidence: 99%